A Review on Underwater Friction Stir Welding (UFSW) - Paramaguru, D. (Pleiades Publishing, 2019)
Underwater Friction Stir Welding (UFSW) is noted as an advanced technique in welding field which is a really new and emerging technology in recent years. In the present paper, a brief explanation on introduction to the Underwater Friction Stir Welding (UFSW) technique along with a review on the latest researches have been made. The review is designed based on joint strength analysis, thermal distribution analysis, microstructural analysis, process modelling and computing techniques, effect of thermal boundary condition in UFSW, effect of process parameters, defects in UFSW and dissimilar welds. The applications of UFSW have also been discussed, along with a detailed description of advantages and limitations of UFSW technique. Lastly, the possible future research exploration has been proposed. Â© 2019, Springer Nature Singapore Pte Ltd.